Potret Kekuatan Perempuan Jawa dalam Bingkai Peralatan Tradisional Masyarakat Jawa Pesisir Melalui Analisis Peran Semantis - M Suryadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This study is aimed to describe the strength of Javanese women in regulating the rhythms of family life. Strength in the form of tenacity and persistence of Javanese women is captured on the symbol of traditional equipment. The symbol of this equipment is stored in the traditional Javanese kitchen. This symbol contains components of material, function, and Javanese philosophy. The method of the research was descriptive qualitative, raising the phenomena of traditional equipment in the life of Javanese women. The method of data collection was by observation, in-depth interviews and demonstration activities. The analytical method used in this research was to decompose the components of the lingual units which are aligned on the standard equipment. The method used to explain the menaning was by the semantic equivalent and analogy.The findings of the research are the novelty of the method, namely the method of interpreting components based on semantic analogies. It was found the strength of Javanese female characters in traditional equipment symbols through understanding concepts and referents. The analysis of the semantic role is able to reveal the relationships of the concepts of the noble values of Javanese culture in the functions of traditional equipment.